sqerferrc - y = (erfc((x-p(1))/p(2)))*p(3)+p(4); sqrerr =

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
function sqrerr = sqerferrc(params,data) f p = double(params); x = [0:1:size(data,2)-1];
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y = (erfc((x-p(1))/p(2)))*p(3)+p(4); sqrerr = sum((double(data)-y).^2);...
View Full Document

This note was uploaded on 01/24/2010 for the course HST. 410J / taught by Professor Alexanderaranyosi during the Spring '07 term at MIT.

Ask a homework question - tutors are online